2009
DOI: 10.1007/s12020-009-9288-6
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and estradiol effects on SRC-1 and SRC-3 expression in human astrocytoma cell lines

Abstract: Progesterone (P(4)) and estradiol (E(2)) regulate many cell functions through their interaction with specific intracellular receptors, which require the participation of coactivators such as SRC-1 and SRC-3 for enhancing their transcriptional activity. Coactivator expression is altered in many cancers and in some of them their expression is regulated by P(4) and E(2). In this study, we determined progesterone and estrogen receptor isoform expression in two human astrocytoma cell lines with different evolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Interestingly, we observed that P increases SRC-1 protein content in D54 cells transfected with shSRC-1 and shControl. Consistent with these observations in our laboratory we have demonstrated that P increases SRC-1 mRNA expression in D54 cells 12 h after its administration, this increase was reflected at SRC-1 protein content 12 h later [17]. This could limit the effects of SRC-1 depletion by shSRC-1 transfection.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Interestingly, we observed that P increases SRC-1 protein content in D54 cells transfected with shSRC-1 and shControl. Consistent with these observations in our laboratory we have demonstrated that P increases SRC-1 mRNA expression in D54 cells 12 h after its administration, this increase was reflected at SRC-1 protein content 12 h later [17]. This could limit the effects of SRC-1 depletion by shSRC-1 transfection.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, it has been reported that PR-A and PR-B modify the expression of different genes in the uterus and breast cancer cells [52]. We have recently reported that P significantly increases SRC-1 expression in D54 cells but not in U373 cells [17]. This suggests a cell-specific modulation of SRC-1 expression by P in astrocytomas that should be related to an increase in transcriptional activation of PR in D54 cells.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations